2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00546
|View full text |Cite
|
Sign up to set email alerts
|

RAVEN: A Dataset for Relational and Analogical Visual REasoNing

Abstract: Dramatic progress has been witnessed in basic vision tasks involving low-level perception, such as object recognition, detection, and tracking. Unfortunately, there is still an enormous performance gap between artificial vision systems and human intelligence in terms of higher-level vision problems, especially ones involving reasoning. Earlier attempts in equipping machines with high-level reasoning have hovered around Visual Question Answering (VQA), one typical task associating vision and language understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
285
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(295 citation statements)
references
References 44 publications
4
285
0
Order By: Relevance
“…Su et al [13] showed that modifying one pixel only could lead up to 73% adversarial success rate depending on the used images. Recently, there is a growing interest in building neural networks that can learn to reason [76][77][78][79]. Saxon et al [77] demonstrated that current state-of-the-art neural networks show moderate performance in solving basic mathematical problems, the performance deteriorates for questions that require the computation of intermediate values.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al [13] showed that modifying one pixel only could lead up to 73% adversarial success rate depending on the used images. Recently, there is a growing interest in building neural networks that can learn to reason [76][77][78][79]. Saxon et al [77] demonstrated that current state-of-the-art neural networks show moderate performance in solving basic mathematical problems, the performance deteriorates for questions that require the computation of intermediate values.…”
Section: Related Workmentioning
confidence: 99%
“…The model was able to solve only 14/40 questions from maths exams for 16 year old schoolchildren in the UK. In [78][79] the researchers tested neural networks ability in structural, relational, and analogical reasoning by trying to solve IQ-like visual questions. In particular, they tested the models on the Raven's Progressive Matrices (RPM) dataset, which is correlated with many aspects of reasoning.…”
Section: Related Workmentioning
confidence: 99%
“…Recently efforts in this direction are started. In [172], a new dataset is proposed based on Raven's Progressive Matrices (RPM) for the task of visual recognition reasoning, comprising images and related RPM problems, with tree-structured annotations. A counting-based dataset is sampled from the available VQA 2.0 and Visual Genome datasets for the task-specific release [200].…”
Section: Datasets For Validating the Explainability In Multimodmentioning
confidence: 99%
“…More recently, a wave of "data-driven Raven's agents" aims to learn integrated representations of visuospatial domain knowl-edge and problem-solving strategies by training on input-output pairs from a large number of example problems (44)(45)(46)(47)(48)(49).…”
Section: Different Types Of Raven's Problem-solving Agentsmentioning
confidence: 99%